Diagnostic Accuracy of Pleural Effusion Mononuclear Cells/Leukocyte Ratio in Tuberculous Pleurisy - Lei, Xiaoli; Wang, Junli; Yang, Zhigang (Frontiers in Medicine, 2021)
Background: Tuberculous pleurisy (TBP) is a common clinical type of tuberculosis (TB) in China. TBP is difficult to diagnose. Whether the mononuclear cell/leukocyte (MNC/LEU) ratio in pleural effusion can contribute to accurate TBP diagnosis remains yet unclear. Objective: To explore the diagnostic value of MNC/LEU ratio in pleural effusion for TBP in China. Methods: This study was a retrospective case-control study involving 406 patients with pleural effusion of unknown cause who were hospitalized at the Henan Provincial People's Hospital. Using histopathological examination of thoracoscopic pleural biopsy as the gold standard for TBP diagnosis, a final total of 215 subjects were included in this study including 91 cases of TBP and 124 cases of non-TBP. The receiver operating characteristic (ROC) curve of pleural effusion MNC/LEU ratio for TBP diagnosis was plotted and the area under curve (AUC) and the optimal cutoff value were determined. In addition, the sensitivity, specificity and accuracy of the MNC/LEU ratio at the optimal cutoff value for TBP diagnosis were also evaluated. Results: The MNC/LEU ratio was significantly higher in TB pleural effusion [95.9% (89.7%-98.0%)] than in non-TB pleural effusion [77.8% (39.3%-93.2%)] (P < 0.001). The AUC was 0.776 (95% CI, 0.714-0.830), and the sensitivity, specificity and accuracy for TBP diagnosis at the 93.7% cutoff value were 64.83%, 79.03% and 0.730, respectively. Conclusion: The pleural effusion MNC/LEU ratio may be a new and valuable laboratory indicator for the diagnosis of tuberculous pleurisy in China.